SPASIALISASI MEDIA DAN DEMOKRATISASI PENYIARAN IMPLEMENTASI SISTEM SIARAN TELEVISI BERJARINGAN DI INDONESIA - Gilang Gusti Aji (SEMIOTIKA: Jurnal Komunikasi, 2014)
The emergence of UU 32/2002 on broadcasting has given hope to the realization of democratic broadcasting system. The new broadcasting system tries to change oligarchy broadcasting system with centralized ownership to share benefit to local society. This aims to reach diversity of content and diversity of ownership aspects. The mandate from broadcasting Constitution is implemented to networked television system. This can be seen from national television which has to own new legal entity in each region, and also can build networked local TV station or cooperate with local TV. But, this system has been delayed several times. Television industry has been adapted to that system which creates some patterns. At one side, centralized ownership is marked by media conglomerates. This phenomenon can threaten democratization process including networked broadcasting system. This research tries to capture its implementation among regions with varied patterns to democratic broadcasting. Keywords :Networked Broadcasting System, Democratization, Spatialization